In situ production of branched glycerol dialkyl glycerol tetraethers in a great basin hot spring (USA) - Zhang, Chuanlun; Wang, Jinxiang; Dodsworth, Jeremy; Williams, Amanda; Zhu, Chun; Hinrichs, Kai-Uwe; Zheng, Fengfeng; Hedlund, Brian P. (Frontiers in Microbiology, 2013)
Branched glycerol dialkyl glycerol tetraethers (bGDGTs) are predominantly found in soils and peat bogs. In this study, we analyzed core-bGDGTs and polar (P-) bGDGTs after hydrolysis of polar fractions using liquid chromatography-atmospheric pressure chemical ionization-mass spectrometry and analyzed intact P-bGDGTs using total lipid extract (TLE) without hydrolysis by liquid chromatography-electrospray ionization-multiple stage mass spectrometry. Our results show multiple lines of evidence for the production of bGDGTs in sediments and cellulolytic enrichments in a hot spring (62-86°C) in the Great Basin (USA). First, in situ cellulolytic enrichment led to an increase in the relative abundance of hydrolysis-derived P-bGDGTs over their Core (C)-bGDGT counterparts. Second, the hydrolysis-derived P- and C-bGDGT profiles in the hot spring were different from those of the surrounding soil samples; in particular, a monoglycosidic bGDGT Ib containing 13,16-dimethyloctacosane and one cyclopentane moiety was detected in the TLE but it was undetectable in surrounding soil samples even after sample enrichments. Third, previously published 16S rRNA gene pyrotag analysis from the same lignocellulose samples demonstrated the enrichment of thermophiles, rather than mesophiles, and total bGDGT abundance in cellulolytic enrichments correlated with the relative abundance of 16S rRNA gene pyrotags from thermophilic bacteria in the phyla Bacteroidetes, Dictyoglomi, EM3, and OP9 (“Atribacteria”). These observations conclusively demonstrate the production of bGDGTs in this hot spring; however, the identity of organisms that produce bGDGTs in the geothermal environment remains unclear.